Pengaruh Model Pembelajaran Market Place Activity Terhadap Kemampuan Menahan Diri Dan Semangat Bekerja Dalam Belajar Pendidikan Agama Islam(Pai) Siswa Kelas X Smk Al Falah Sampang - Sunarjo; Syamsul Arifin; Sucipto (Penerbit STKIP PGRI Bangkalan, 2025)
The findings in the field show that currently the learning process that occurs, especially at Al Falah Vocational School in Sampang, is still mostly carried out by presenting verbal information, where teachers teaching in class still do not use learning methods that are not yet optimal. Based on the results of temporary observations, only around 30% use innovative learning methods, so the impact is that learning outcomes are still below the KKM, where of the 22 students, the PAI lesson scores are 15 students or 70% of the scores are still below the KKM. In line with the explanation above, it is necessary to carry out innovative learning. One way that can make students active in the learning process is by applying varied learning models (Riswati, Alpusari, Marhadi, 2018). One learning model that is related to the ability to restrain oneself and enthusiasm for working in learning PAI is the Market Place Learning Model Activity. The formulation of the problem is: Is there an influence of the Market Place Activity Learning Model on the ability to restrain oneself and enthusiasm for working in learning PAI for Class X students at Al Falah Vocational School, Sampang? The aim is to determine the influence of the Market Place Activity Learning Model on the ability to restrain oneself and enthusiasm for working in learning PAI for Class X students at Al Falah Vocational School, Sampang. The type of research used in this research is quantitative, quantitative research is often also referred to as being present or expressed in the form of numbers obtained from the field, or it can also be called qualitative data which is expressed in the form of numbers obtained by changing qualitative values into quantitative values. Based on the output above, it is known that the Pillai's Trace, Wilks' Lambda, Hotelling's Trace and Roy's Largest Root test results have sig values. 0.000 < 0.05. This means that